DCS and spin polarization parameter of argon by electron impact - Verma, Keshav R; Sharma, Kamlesh K; Saxena, S (International Multidisciplinary Research Journal, 2012)
In present paper, differential scattering cross section (DCS) and spin polarization parameter (S) of the elastic scattering of slow electrons from argon are reported and comparison is made with different available theoretical and experimental data. The present calculation is done with R-matrix theory. We have chosen a complex type potential, a part of which is directly calculated from the target charge density and other part is taken from Baluja and Jain [1]. The present work yields a satisfactory result for differential cross section and spin polarization parameter while previously large discrepancies were found in theoretical and experimental data.